Spectrum of lung pathology in medicolegal autopsies at rural teaching hospital: A two-year study - Kale, Apurva; Passi, Rashim; Karle, Ravindra R. (International journal of health sciences, 2022)
Background: Lungs are the major organs involved by a number of infectious, inflammatory and occupational hazards. They are also involved secondarily by all forms of terminal events like cardiovascular events. Autopsy is a part of pathology that serves as an important tool to identify the cause and manner of death and to learn about methods to prevent them. Methods: This is a retrospective study conducted on the autopsy specimens received in the department of pathology from 1 January 2020 to 31 December 2021. Gross findings were noted at the time of autopsy and the specimen was subjected to routine histopathological processing and hematoxylin and eosin staining. Histopathological findings were noted. Results: Out of total 78 cases, 30.17% shows Congestion and oedema, 24.65% shows Pneumonia. 10.95% and 8.21% shows interstitial changes in the form of interstitial pneumonia or mononuclear interstitial infiltrate and Diffuse alveolar damage respectively, 6.84% shows emphysematous changes and 5.84% shows chronic passive venous congestion. 4.1% cases shows findings of tuberculosis and only 1 case was of lung abscess, metastatic papillary renal cell carcinoma and fibrin thrombi each. Highest number of cases (32) belonged to 16-30 age group. Least number of cases (2) were from >75 age group.